2015
DOI: 10.1126/scitranslmed.aaa0072
|View full text |Cite
|
Sign up to set email alerts
|

Timely and spatially regulated maturation of B and T cell repertoire during human fetal development

Abstract: Insights into the ontogeny of the human fetal adaptive immune system are of great value for understanding immunocompetence of the developing fetus. However, to date, this has remained largely uncharted territory, in large part because blood samples from healthy, early gestation fetuses have been hard to come by. In a comprehensive study, we analyzed levels of T cell receptor excision circles (TRECs), signal-joint κ receptor excision circles (sjKRECs), and intron recombination signal sequence-K-deleting element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
144
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(164 citation statements)
references
References 55 publications
15
144
3
2
Order By: Relevance
“…Also, the majority of antibodies isolated from the youngest three infants lacked SHM, similar to what was observed previously in postF-reactive B cells (Williams et al, 2009). However, nearly 5% of antibodies isolated from these infants had VH genes containing at least five nucleotide substitutions, consistent with previous studies showing that SHM does occur in young infants, albeit at relatively low frequency (Rechavi et al, 2015; Ridings et al, 1998). The level of SHM in antibodies isolated from the two infants ≥ 6 mo.…”
Section: Resultssupporting
confidence: 90%
“…Also, the majority of antibodies isolated from the youngest three infants lacked SHM, similar to what was observed previously in postF-reactive B cells (Williams et al, 2009). However, nearly 5% of antibodies isolated from these infants had VH genes containing at least five nucleotide substitutions, consistent with previous studies showing that SHM does occur in young infants, albeit at relatively low frequency (Rechavi et al, 2015; Ridings et al, 1998). The level of SHM in antibodies isolated from the two infants ≥ 6 mo.…”
Section: Resultssupporting
confidence: 90%
“…In addition to thymic B cells, we also report, to our knowledge for the first time, on the reactivity of fetal BM-derived B cells. Although the repertoire of fetal B cells has been documented extensively (35,(39)(40)(41)(42)(43), the suggestion that these genes would encode autoreactive Abs has not been addressed before (44)(45)(46). In the present study, we showed that fetal B cell-derived Abs bind stronger to dsDNA than do pediatric BM-derived B cells.…”
Section: Discussionmentioning
confidence: 49%
“…45,46 Recently, Rechavi et al have shown that fetal-derived lymphocytes also have reduced numbers of numbers of N-nucleotides in IgH and TRB rearrangements. 47 In addition, they showed preferential use of the DH-proximal VH genes IgHV6-1 and IgHV1-2 and the JH-proximal IgHD7-27 genes in the fetal IgH rearrangements. In contrast, the use of IgHV6-1, IgHV1-2, and IgHD7-27 was normal in the XLF-deficient patients (data not shown), suggesting it is not likely that the XLFdeficient patients have an increased frequency of the fetal-derived lymphocytes.…”
Section: Discussionmentioning
confidence: 98%